2017
DOI: 10.4236/ars.2017.61002
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study among Different Semi-Empirical Models for Soil Salinity Prediction in an Arid Environment Using OLI Landsat-8 Data

Abstract: Salt-affected soils, caused by natural or human activities, are a common environmental hazard in semi-arid and arid landscapes. Excess salts in soils affect plant growth and production, soil and water quality and, therefore, increase soil erosion and land degradation. This research investigates the performance of five different semi-empirical predictive models for soil salinity spatial distribution mapping in arid environment using OLI sensor image data. This is the first attempt to test remote sensing based s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 13 publications
2
10
1
Order By: Relevance
“…However, the reflectance changed proportionally as the salt concentrations increased in the soil samples from 26 to 507 dS/m (Table 3). This observation is consistent with many other studies indicating the importance of the spectral domain between 1200 and 2500 nm for soil salinity characterization [18,[52][53][54]. Table 3.…”
Section: Spectral and Laboratory Analysessupporting
confidence: 92%
See 1 more Smart Citation
“…However, the reflectance changed proportionally as the salt concentrations increased in the soil samples from 26 to 507 dS/m (Table 3). This observation is consistent with many other studies indicating the importance of the spectral domain between 1200 and 2500 nm for soil salinity characterization [18,[52][53][54]. Table 3.…”
Section: Spectral and Laboratory Analysessupporting
confidence: 92%
“…In addition, the spatiotemporal dynamic nature of soil salinity makes it very difficult to use conventional methods for comparisons over large territory [5]. Several authors have examined the advantages of remote sensing methods and sensors for the assessment of soil degradation due to salinity [1, [6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Remote sensing methods are relatively easy to apply and reliable in certain conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The NDSI based model performed accurately in predicting and mapping medium salinity levels (100%) and low saline soils (33%)). The SSSI-1 and SSSI-2 based models in this study demonstrated conflicting results to those shown in [49].…”
Section: Maps Verificationcontrasting
confidence: 86%
“…Statistical and mathematical models have been developed to model vegetation canopies [47], soil moisture [48] and soil salinity [46], [49]. A widely used technique in the estimation of soil salinity in arid and semi-arid regions is the application of empirical and semi-empirical soil salinity models [46], [49].…”
Section: Empirical Models Developmentmentioning
confidence: 99%
“…The remote-sensing method is also known as an effective approach for determining the spatial distributions of soil salinity, classifying the soil salinity levels due to the diagnostic spectral characteristics of different salt minerals [11][12][13][14]. However, it is often used only in a qualitative way because of the mixed pixel problems and the low spectral resolution of most remote-sensing data [15][16][17]. Therefore, it is urgent and important to develop a non-destructive and rapid method to measure the salt content based on the chemical and physical properties of the saline soils.…”
mentioning
confidence: 99%